Regional financial cooperation - Ocampo, José Antonio; United Nations. Economic Commission for Latin America and the Caribbean; ebrary, Inc. ([Santiago, Chile?] : United Nations Economic Commission for Latin America and the Caribbean ; Washington, D.C. : Brookings Institution Press, 2006)
"Assesses how regional financial institutions can help developing countries, often at a disadvantage within the global financial framework, finance their investment needs, counteract the volatility of private capital flows, and make their voices heard"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Regionalism -- Developing countries; International economic relations; Developing countries -- Economic integration; Developing countries -- Foreign economic relations; Electronic books